MEKANISME PENAWARAN UMUM DI PASAR MODAL - Muhammad Wahyudi; Utari Isma Sitorus; Putri Handayani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2022)
The contribution of the capital market to the economy of a country is very important because investing in the capital market provides functions in the economy and finance, the capital market is said to have an economic function because it provides facilities or vehicles that bring together the interests of those who have the advantage of funds and those who need funds. With the corporate capital market, public companies can obtain funds from the public through sales. Part of the financial function of the capital market is to provide the possibility and opportunity to make a profit.